Effect of COVID-19 pandemic on global Bariatric surgery PRActiceS – The COBRAS study. Issue 4 (July 2021) - Singhal, Rishi; Tahrani, Abd A.; Sakran, Nasser; Herrera, Miguel; Menon, Vinod; Khaitan, Manish; Foschi, Diego; Super, Jonathan; Sandvik, Jorunn; Angrisani, Luigi; Kawahara, Nilton; Teixeira, Julio; et al.
Highlights: Significant reduction in the volume of bariatric procedures globally. High morbidity and mortality from bariatric procedures performed during the pandemic. Disparity in the availability of Personal Protective Equipment globally. Safeguards to allow for a safe resumption of bariatric surgery reported. Abstract: Introduction: There is a paucity of data in scientific literature on the impact of Coronavirus Disease 2019 (COVID-19) pandemic on bariatric surgery. The aim of this study was to evaluate the impact of COVID-19 pandemic on Bariatric Surgery globally. Methods: We conducted a global online survey of bariatric surgeons between 16/04/20 – 15/05/20. The survey was endorsed by five national bariatric surgery societies and circulated amongst their memberships. Authors also shared the link through their personal networks, email groups, and social media. Results: 703 respondents from 77 countries completed the survey. Respondents reported a drop in elective bariatric activity from a median (IQR) of 130 (60–250) procedures in 2019 to a median of 0 (0–2) between16/03/2020 and 15/04/2020 during the pandemic. The corresponding figures for emergency activity were 5 (2–10) and 0 (0–1) respectively. 441 (63%) respondents did not perform any bariatric procedures during this time period. Surgeons reported outcomes of 61 elective bariatric surgical procedures during the pandemic with 13 (21%) needing ventilation and 2 (3.3%) deaths. Of the 13 emergency bariatric procedures reported, 5 (38%) needed ventilation and 4 (31%) died. 90 (13%) surgeons reported having had to perform a bariatric surgical or endoscopic procedure without adequate Personal Protective Equipment. Conclusions: COVID-19 pandemic led to a remarkable decline in global elective and emergency bariatric surgery activity at its beginning. Both elective and emergency procedures performed at this stage of the pandemic had considerable morbidity and mortality.